Inflation volume‐balloon diameter and inflation pressure‐balloon diameter characteristics of commonly used bronchial blocker balloons for single‐lung ventilation in children. Issue 4 (11th February 2021) - Goetschi, Markus; Kemper, Michael; Kleine‐Brueggeney, Maren; Dave, Mital H.; Weiss, Markus
Abstract: Background: Balloon‐tipped bronchial blocker catheters are widely used in pediatric thoracic anesthesia to establish single‐lung ventilation. In clinical practice, their balloons demonstrate sudden expansion when inflated with air. In addition, there are concerns related to the high inflation pressures required to expand the balloons. Methods: This in vitro study assessed inflation volume‐ and inflation pressure‐balloon diameter characteristics of the Fogarty arterial embolectomy catheters and Arndt endobronchial blockers. Balloon diameters were photographically assessed during unrestricted volume‐ and pressure‐guided inflation, using air up to the maximum allowed inflation volume as indicated by the manufacturers. Inflation pressures required to open the blocker balloons and inflation pressures needed to expand them to maximum indicated diameter were measured. Results: Volume‐guided inflation demonstrated a late acute rise in diameter in Fogarty blocker balloons, whereas in the Arndt endobronchial blocker balloons almost linear inflation volume‐to‐diameter characteristics were observed. Pressure‐guided inflation on the other hand demonstrated low‐volume, high‐pressure characteristics in the Fogarty blocker balloons, with inflation pressures required to expand the balloons to maximum diameters ranging from (mean (SD)) 636 (75) to 947 (152) cmH2 O. The inflation pressures required to open the Fogarty blocker balloons were even >1000 cmH2 O. Inflation pressures required to expand the 5 F, 7 F, and 9 F Arndt endobronchial blocker balloons to maximum indicated diameter were much lower, namely at 218 (15), 252 (28), and 163 (8) cmH2 O. Conclusion: Based on these study findings, the balloons of Fogarty arterial embolectomy catheters represent high‐pressure devices and do not permit stepwise controlled bronchial blockage. The Arndt endobronchial blockers have some advantages over the Fogarty blocker devices, but also represent high‐pressure equipment and must be used with caution and limited duration. Manufacturers are asked to design pediatric endobronchial blocker catheters with truly high‐volume, low‐pressure balloons in accordance to age‐related pediatric airway dimensions.